The Scope of Hospital-Based Simulation. (February 2021) - Gilbert, Marie; Waxman, KT; Gilbert, Gregory E.; Congenie, Kari
Abstract : BACKGROUND: Healthcare simulation has expanded dramatically; however, little is known about the scope of simulation in acute care hospitals. METHODS: A descriptive, cross-sectional online survey was used. Participants included nurse executives from acute care hospitals in California. RESULTS: Most organizations (96%) used simulation primarily for education, 37% used simulation for health system integration and systems testing, 30% used it for error investigation, 15% used it for research, and 15% used it for patient/family education. CONCLUSIONS: Organizations have a substantial opportunity to increase the scope of simulation beyond education to include systems integration, clinical systems testing, and other translational simulation activities. This targeted focus on patient safety and quality will allow hospitals to improve financial performance and maximize scarce resources.